Pengaruh Kegiatan Menganyam terhadap Kemampuan Motorik Halus Anak Usia Dini - Putri Az-Zahra; Taty Fauzi; Dessi Andriani (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the effect of weaving activities on the fine motor skills of children in group B at Barokah Gading Early Childhood Education. This type of research is a Pre-Experimental research with the type of One-Group Pretest-Posttest Design by providing treatment using weaving activities in children, then comparing fine motor skills in children before and after being given weaving activities. The method used in collecting research data is through a checklist observation sheet. The research data analysis method is t-test. The study population was all 15 children in group B and 15 children in group B as samples. The results showed that there was an effect of weaving activities on the fine motor skills of children in group B in PAUD Barokah Gading. This is evident from the results of the calculation of the hypothesis, based on the calculations obtained from the posttest test results of the normality of the data, these variances are homogeneous. Then the normality test of the homogeneity data was carried out and it was stated that the data was normally distributed and the variance of this study was homogeneous, then hypothesis testing was carried out from the results of the t-test calculation above, the value of tcount > ttable or 19.659 > 2.145 was rejected. the effect of weaving activities on the fine motor skills of group B children in PAUD Barokah Gading.